A Premature Stop Codon in RAF1 Is the Priority Candidate Causative Mutation of the Inherited Chicken Wingless-2 Developmental Syndrome - Youngworth, Ingrid (Genes (Basel), 2019)
The chicken wingless-2 (wg-2) mutation is inherited in an autosomal recessive fashion, and the resulting phenotype in mutant (wg-2/wg-2) individuals is a developmental syndrome characterized by absent wings, truncated legs, craniofacial as well as skin and feather defects, and kidney malformations. Mapping and genotyping established that the mutation resides within 227 kilobases (kb) of chromosome 12 in a wg-2 congenic inbred line. A capture array was designed to target and sequence the candidate region along with flanking DNA in 24 birds from the line. Many point mutations and insertions or deletions were identified, and analysis of the linked variants indicated a point mutation predicted to cause a premature stop codon in the RAF1 gene. Expression studies were conducted inclusive of all genes in the candidate region. Interestingly, RAF1 transcription was elevated, yet the protein was absent in the mutants relative to normal individuals. RAF1 encodes a protein integral to the Ras/Raf/MAPK signaling pathway controlling cellular proliferation, and notably, human RASopathies are developmental syndromes caused by germline mutations in genes of this pathway. Our work indicates RAF1 as the priority candidate causative gene for wg-2 and provides a new animal model to study an important signaling pathway implicated in limb development, as well as RASopathies.